Негативна дисперсiя швидкостi високочастотного звуку у водних розчинах неелектролiту в околi концентрацiї особливої точки - Sabirov, L. M.; Semenov, D. I.; Khaydarov, Kh. S. (Publishing house "Academperiodika", 2019)
A new method of determination of the hypersound velocity dispersion is proposed. It is based on the direct measurement of the frequency shift of Brillouin components in the light scattering spectra registered at different angles. The concentration dependence of the hypersound velocity dispersion is studied in 4-methylpyridine-water solutions. Negative dispersion is experimentally observed in the region of the singular point concentration.